LUNTURNYA PERMAINAN TRADISIONAL BAGI ANAK DI DESA TEPUS GUNUNG KIDUL - Feri Budi Setyawan; Ella Kusuma Wardani; Ikhwani Mukmin; Aprilia Cyahyani Rupilu; Yessi Ika Sari (LPPM STKIP PGRI Sidoarjo, 2023)
At this time, the existence of advanced technology can quickly change the mindset and social life in society. One of them is a traditional game that has begun to fade and be left aside by the existence of modern games. Now, children prefer modern games compared to traditional games. With the advancement of science and technology, play is no longer a physical activity in the growth and development of a child. In this study using descriptive qualitative methods, analyzing social facts. So it can be concluded that there is a shift in culture and values towards a game, lack of interest in traditional games due to the absence of challenges in a game and environmental influences and interaction patterns that cause no direct contact of children while playing